Một cách giải bài toán dựa trên mạng ngữ nghĩa các công thức - Anh, Đỗ Hồng; Kiếm, Hoàng (Journal of Computer Science and Cybernetics, 2016)
This paper presents a method for creating a knowledge base (formulas network), drawing inference over this built-in base, finding and computing one/more solutions to your problem in  orienting your domains of interest. Tutor Euclide is the firth prototype vertion in this approach.